Oral health status of people with mental disabilities in the municipality of Banja Luka - Ilić Sanja; Đeri Aleksandra; Pašagić Ljubica; Pavlić Verica; Janković Ognjenka (Serbian Medical Society - Dental Section, Belgrade, 2014)
Introduction. Oral health of mentally disabled people in Republika Srpska is on very low level. The greatest number of these persons is often edentulous or with a small number of teeth with extensive caries, high DMFT index and severe periodontal diseases. The aim of this study was to determine oral health status of people with mental disabilities in the municipality of Banja Luka. Material and Methods. Study included 95 patients (45 females and 50 males), aged 15 to 45 years. The subjects were divided into two groups according to the degree of mental impairment: ICD-10 F71 (65 respondents) and F72 (30 respondents). Dental assessment included: number of present teeth, presence of caries, restorations, number of extracted teeth, presence of residual roots, fractures, presence and number of fixed restorations, gingival and plaque index. Results. The mean DMFT index in patients with severe mental disability was high (17.4), while it was 12.3 in patients with mild disability. The mean value of person caries index (PCI) was 100%. In addition, the mean value of teeth caries index (TCI) in severely disabled persons was 58.1 whereas in those with mild intellectual disability it was 42.4. Average caries index (ACI) in patients with severe mental disability was 16.9 while in the group of patients with mild disability this value was 10.2. Plaque index in severely disabled people was 2.4, while in the second group (mild disability) it was 1.9. Gingival index in patients with severe mental disability was 1.8 and in mild disability group it was 1.3. Conclusion. People with mental disabilities in the municipality of Banjaluka have poor oral health. They do not have habits, attitudes and behavior towards oral health.